Microbial community structure and metabolic characteristics in sediments from five different deep-sea trenches - Xiao, Yao; Liu, Hao; Wu, Ziying; Li, Xuegong; Jing, Hongmei (Frontiers in Microbiology, 2025)
Microbial community growth efficiency, defined as the ratio of production to substrate assimilation, could provide insights into carbon flow among microbes and the regulation of marine biogeochemical cycles. However, the metabolic characteristics of microbes in deep-sea trenches remain largely undetermined. In this study, the structural and metabolic characteristics of microbial communities in five deep-sea trenches were investigated using Illumina high-throughput sequencing, quantitative PCR, the 3H-leucine incorporation method, and electron transport system analysis. We found that microbial community structure and functional gene abundance exhibited significant inter-trench variations, indicating that geographic isolation and environmental filters are key drivers of microbial biogeography. Under atmospheric pressure (AP), significantly higher respiration rates in the Mariana (MT) and Yap (YT) trenches than in the Kermadec (KT), Diamantina (DT), and Wallaby-Zenith (WT) trenches showed that higher organic carbon input in the western Pacific supported more active heterotrophic metabolism. Crucially, the consistently lower prokaryotic growth efficiency (PGE) under high hydrostatic pressure (HHP) across all trenches indicated that, in situ, pressure fundamentally shifted carbon allocation from biomass production to maintenance respiration, drastically constraining deep-sea carbon conversion efficiency. This demonstrated that genomic potential alone was insufficient to predict carbon cycling rates, and that direct physiological measurements under in situ conditions were essential for accurate assessment. Our study provided preliminary insights into the processes and efficiency of microbial-driven carbon cycling in the deep biosphere.